Complementary and contingent value of SMEs' data capability and supply chain capability in the competitive environment - Hautala-Kankaanpää, Tuire (Emerald, 2023)
Purpose Scholars and practitioners increasingly recognize data as an important source of business opportunities, but research on the effect on small and medium-sized enterprises (SMEs) is limited. This paper empirically examines the complementary impact of SMEs' data capability and supply chain capability (SCC) and further tests the mediation effect of SCC between data capability and operational performance. The mediated effect of data capability is also moderated by competition. Design/methodology/approach This paper analyzes longitudinal data collected from 122 manufacturing SMEs in Finland. Hypotheses were tested by using structural equation modeling (SEM). Findings The results show that to benefit from the data capability, SMEs require a certain level of SCC to extract the value from the SMEs' data capability and support operational performance. Additionally, competition affects how SMEs benefit from data capability, as competitor turbulence moderates the complementary effect of data capability and SCC on operational performance. Originality/value This is one of the first studies examining the longitudinal effect of SMEs' data and SCC on operational performance in the current competitive environment.
Keywords: Data capability; Supply chain capability; Operational performance; SME; Competition; competition (economy); fi=Strateginen johtaminen|en=Strategic Management|